People with disabilities in the labor market: Facilitators and barriers. - Toldrá, Rosé Colom; Santos, Maria Conceição (Work, 2013)
BACKGROUND: Participation in the workforce is one of the main social evaluations all individuals are subject to in modern society. Public policies supporting social justice for persons with disabilities have gained prominence in several nations in the last decades and it is critical to ensure that those who want to work are afforded the opportunity to do so. Meanwhile they remain under represented in the labor market within the contemporary world. OBJECTIVE: The purpose of this study was to identify facilitators or barriers faced by people with disability within the workforce. PARTICIPANTS: Ten workers with disabilities from various companies and performing diverse professional job functions participated in semi-structured interviews. METHOD: The Discourse of the Collective Subject method was employed as a means to organize and analyze qualitative data of a verbal nature. RESULTS: Reasonable work conditions, adjustments, and accommodations facilitate performance and job retention. Social participation through employment leads to social recognition and the feeling of citizenship. On the other hand prejudice, unequal opportunities, workers' low educational attainment, and lack of training opportunities lead to employment exclusion.CONCLUSION: To include people with disabilities in the workforce, it is necessary to focus on attaining equal levels of education, an unbiased and inclusive process for entering the labor market, and continued management of disability issues within the workplace. Together, these elements create equal opportunities for workers with disabilities to advance in their careers, which in turn enables participation, social recognition and guaranties their rights as citizens.